2020
DOI: 10.21873/invivo.11837
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Monitoring Physical Function for Quality of Life Assessments in Hematopoietic Stem Cell Transplantation Patients: A Prospective Cohort Study

Abstract: Background/Aim: Physical function is known to decrease after hematopoietic stem cell transplantation (HSCT), with the most substantial impairment noted at 90 days post-transplantation. Little is known about the natural course of physical function during the acute post-transplant period preciously. The aim of the study was to monitor the changes in physical function through serial evaluations of the physical function, and identify the effect of physical function on QoL during the acute post-transplant period. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…Our study showed that impaired PF in the acute post-transplant period of HSCT during hospitalization occurs in over a third of the recipients, mainly in the rst week after HSCT. In our previous study with 41 participants, 24.40% of patients experienced a decline in PF after HSCT [20]. Few studies have investigated PF changes after HSCT during the inpatient period.…”
Section: Discussionmentioning
confidence: 91%
“…Our study showed that impaired PF in the acute post-transplant period of HSCT during hospitalization occurs in over a third of the recipients, mainly in the rst week after HSCT. In our previous study with 41 participants, 24.40% of patients experienced a decline in PF after HSCT [20]. Few studies have investigated PF changes after HSCT during the inpatient period.…”
Section: Discussionmentioning
confidence: 91%
“…International studies show higher age means of the patients undergoing HSCT. Two South Korean studies have identified means over 48 years old (Kang et al, 2020;Kim et al, 2020). An Italian study found a mean of 50 years old (Biagioli et al, 2019), and a research study conducted in the United States found a mean of 56 years old (LaLonde et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…AHSCT is associated with health problems occurring in the immediate post-transplant period including infections, bleeding, mucositis, fever, nausea, hypotension and shock, skin rash, acute or chronic pain and diarrhea 4 which can negatively affect patients’ QoL and survival. 5 …”
Section: Introductionmentioning
confidence: 99%
“…3 AHSCT is associated with health problems occurring in the immediate post-transplant period including infections, bleeding, mucositis, fever, nausea, hypotension and shock, skin rash, acute or chronic pain and diarrhea 4 which can negatively affect patients' QoL and survival. 5 In addition, patients undergoing an AHSCT can present relevant psychological distress-most common depression, anxiety and sleeping problems-they might confront with primitive defence mechanisms such as denial, and projection. 6 Depression is the most common manifestation of psychological distress in patients with neoplastic disease; [7][8][9] which is even more frequent in patients with advanced disease.…”
mentioning
confidence: 99%